DESARROLLO DE UN SISTEMA DE GESTIÓN DE INVENTARIOS PARA EL CONTROL DE MATERIALES, EQUIPOS Y HERRAMIENTAS DENTRO DE LA EMPRESA DE CONSTRUCCIÓN REALIDAD COLOMBIA S.A.S - Santiago Parra Angel; Ever Ángel Fuentes Rojas (Revista Ingeniería, Matemáticas y Ciencias de la Información)
The company Realidad Colombia SAS is dedicated to the contracting and execution of civil works, especially in thedepartment of Risaralda. Currently, it is developing its work in the Terragrata condominium in the city of Dosquebradas,in the process of execution of the work, some delays, losses and reprocesses have been evidenced, which imply a greaterinvestment of human capital and financial resources; based on the records that the company manages, it has been foundthat the low control in the warehouse in the last quarters is one of the main inefficiency factors, due to the fact that thereis not a defined system in terms of inventory control, likewise there is no stipulated record with a physical or magneticdocumentary support that allows verifying the amount of input and output of the products that are in work, this situation generates an economic problem of all kinds, from the waste of material to delays in the execution time. Taking intoaccount the above, work was done in the warehouse area, since it is the means by which the execution of the work iscarried out, an investigation was made about which method of inventory control is more beneficial to the organization,thus providing the company with a system that controls the references of products, equipment and tools identifying theirlocation, destination and the time they are used, optimizing time between orders, achieving that in the case of steelbetween 40 and 43 orders are requested annually and thus reducing costs of maintaining and ordering.